Penggunaan Mikrokontroller Water Level terhadap Peringatan Luapan Limbah Beton Cair Batching Plant di Industri Konstruksi Yogyakarta - ramadhani, fadhila veby; Yamtana, Yamtana; Rois, Ibnu; Istiqomah, Siti Hani (Jurnal Kesehatan Lingkungan Mandiri, 2024)
Background: Liquid waste that is not properly disposed of and managed can have a negative impact on the environment. The frequent negligence of employees in monitoring the full sediment pond causes the wastewater to flow to the ground surface area and can flow into the river. The existence of this Microcontroller Water level tool serves as a warning of overflow of liquid concrete batching plant waste.Objective: Find out the effect of using a water level microcontroller on warning the overflow of liquid concrete batching plant waste in the construction industry of Yogyakarta. Method: The type of research used in this study is a quasi-experiment with a Posttest Only Design or research design. The research was conducted in the industrial liquid concrete waste storage pond of Yogyakarta construction industri. Result : Mikrokontroller Water Level has a successful performance as a warning of overflow of liquid concrete batching plant waste with an average accuracy value of 100%. It can be stated that the water level microcontroller tool is effective as a warning notification of batching plant liquid waste overflow. The results show that there is an effect of using a microcontroller tool on warning the overflow of liquid concrete batching plant waste. Conslusion : Microkontroller water level device has successful performance as a warning of overflow of liquid concrete batching plant waste at Yogyakarta construction industri.